PREVENTION AND CONTROL MEASURES IN DENTISTRY UNDER COVID-19 CONDITIONS - V. P. Litovchenko (Eastern Ukrainian Medical Journal, 2020)
Introduction. Given the worldwide spread of acute respiratory disease COVID-19, the WHO announcement of a pandemic and unprecedented quarantine restrictions in March 2020, the problem of organizing measures to prevent the emergence and spread of COVID-19 becomes particularly relevant and undergoes significant additions and improvements. It should be noted that the risk of transmission of coronavirus disease during dental procedures is defined as extremely high, due to close doctor-patient contact, the use of specific equipment (turbine tip, ultrasonic scaler, airflow, etc.), interaction with biological fluids, including saliva and tissues. At the same time, acute conditions in patients require emergency dental care. In such conditions, it is necessary to comply with anti-epidemic measures, use sterilization procedures for all categories of instruments, as well as the introduction of additional convenient and modern measures to prevent cross-contamination in dental institutions, including checklists, questionnaires and so on. Purpose. Based on the analysis of theoretical and clinical aspects of the problem of asepsis in the face of new challenges, we aimed to develop an author’s "case" of standardized checklists to ensure dental care in the spread of SARS-CoV-2. Methods. Theoretical analysis of literature sources and results of modern research presented in electronic scientific publications included in scientometric databases, such as PubMed, Index Copernicus, Ulrich’s Periodicals, Google Scholar, Web of Science, Scopus, Medline, etc.; generalization of knowledge and practical experience gained during training on the basis of the Dental Medical Center of the National Medical University named after O. O. Bogomolets; survey of respondents using Google forms. Results. In the context of dental care, the features of dangerous infectious diseases (routes of transmission, resistance, etc.) and appropriate preventive measures were analyzed. The clinical aspects of сoronavirus disease (COVID-19) were considered in detail. As additional anti-epidemic measures (control measures), the author’s "case" of checklists was presented: "Assessment of urgency of dental care," "Assessment of risks of possible infection with Covid-19" (to be completed before and 24 hours after treatment). Conclusions. General and specific precautions are crucial for minimizing the spread of COVID-19 coronavirus disease. Additional solutions are important, including a thorough preliminary examination of patients, including the use of the proposed "case" of checklists (77.4% of respondents from 53 practicing dentists noted the relevance of such questionnaires in their practice) and enhanced asepsis, especially if treating patients with confirmed COVID-19 will be necessary. The main preventive measures aim to prevent other infections (HIV, hepatitis, etc.), the risk of transmission of which increases in the dental office.